Liquid biopsy in the practice of neo-oncology - Geva, Smadar; Roisman, Laila C.; Peled, Nir (Journal of Thoracic Disease; Vol 8, No 10 (October 01, 2016): Journal of Thoracic Disease, 2016)
Selecting the optimal platform for molecular diagnostic profiling is a crucial step in the management of patients with advanced lung adenocarcinomas. With an ever-expanding number of targetable oncogenic drivers, there was an evolution of molecular diagnostic platforms. Molecular testing previously followed a one-driver-one-test approach, with the use of Sanger sequencing, reverse transcription polymerase chain reaction (RT-PCR), fluorescence in situ hybridization (FISH) or Immunohistochemistry. Multiplex PCR-based platforms were developed to simultaneously interrogate multiple oncogenes, however these assays only detect the expression of selected known hotspot mutations and oncogenes and do not have the ability to discover new or additional drug targets (1,2). Nextgeneration sequencing (NGS), also known as massively parallel sequencing, represents an effective way to capture a large amount of genomic information about a cancer (3). In addition to known hotspot oncogenic mutations or gene rearrangements in non-small cell lung cancer (NSCLC), NGS has also identified genetic abnormalities that are previous known in other cancer types as well and uncovered many novel genetic abnormalities without knowledge of their biologic functions (2). The use of NGS has also resulted in the identification of new actionable genomic alterations as well as uncovered false negative tests in close to two thirds of lung adenocarcinomas that previously tested “negative” for known alterations by multiple conventional non-NGS tests (1,4-6).